Localization of ionization-induced trapping in a laser wakefield accelerator using a density down-ramp. (23rd March 2016) - Hansson, M; Audet, T L; Ekerfelt, H; Aurand, B; Gallardo González, I; Desforges, F G; Davoine, X; Maitrallain, A; Reymond, S; Monot, P; Persson, A; Dobosz Dufrénoy, S; et al.
Abstract: We report on a study on controlled trapping of electrons, by field ionization of nitrogen ions, in laser wakefield accelerators in variable length gas cells. In addition to ionization-induced trapping in the density plateau inside the cells, which results in wide, but stable, electron energy spectra, a regime of ionization-induced trapping localized in the density down-ramp at the exit of the gas cells, is found. The resulting electron energy spectra are peaked, with 10% shot-to-shot fluctuations in peak energy. Ionization-induced trapping of electrons in the density down-ramp is a way to trap and accelerate a large number of electrons, thus improving the efficiency of the laser-driven wakefield acceleration.